Flexible capacitive behavior of hybrid carbon materials prepared from graphene sheets. (6th June 2016) - Ding, Y-H; Xie, W; Zhang, P; Jiang, Y
Abstract: High frequency ultrasonication was employed to reduce the aggregation of graphene by constructing hybrid carbon materials (HCMs), which are endowed with a large electrochemical reaction area and high energy density. HCMs exhibited a specific capacitance of 168.5 F · g −1 with ∼100% capacitance retention over 500 cycles. Flexible supercapacitors fabricated from HCMs also showed an excellent capacitive behavior even under tough conditions. These outstanding electrochemical properties were ascribed to the increased specific surface area and open structure of HCMs.